2008
DOI: 10.1596/1813-9450-4576
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital And The Changing Structure Of The Indian Economy

Abstract: on output in the service sectors. They do not find any such effect for the manufacturing sectors. The paper shows that the differential effect on services and manufacturing arises because service sectors are more skill intensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…Without additional controls, Amin and Mattoo (2008) find a positive and significant effect of human capital (enrollments at the national level) on value added in total manufacturing and registered manufacturing. However, these statistically significant effects do not survive robustness checks or addition of full control variables.…”
Section: A Brief Theoretical Framework and The Review Of The Literaturementioning
confidence: 82%
“…Without additional controls, Amin and Mattoo (2008) find a positive and significant effect of human capital (enrollments at the national level) on value added in total manufacturing and registered manufacturing. However, these statistically significant effects do not survive robustness checks or addition of full control variables.…”
Section: A Brief Theoretical Framework and The Review Of The Literaturementioning
confidence: 82%
“…The universities are a significant driver of economic growth and can result in innovation and creation of patents. Amin and Mattoo (2008) established that in India highly skilled labour, measured by the enrollments in the tertiary sector, had a positively significant effect on the services sector growth.…”
Section: 1discussion On Well-being Indexmentioning
confidence: 99%
“…The findings showed that governance and economic policies both explain differential level of development across the states in India. Amin and Mattoo (2008) examined the role of human capital for 14 Indian states for the period 1980-2000. Their study noted that the availability of skilled workers had a greater impact on the services sector output than manufacturing or agriculture as it is more skill intensive.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In this paper, we not only bridge this gap in research but also challenge existing literature by suggesting that services growth in India may be 2 Some work has been done by Wu Yanrui (2004), Deepita Chakravarty (2005) and Amin & Mattoo (2008). equalizing in the long run. To substantiate our claim, we employ both standard growth regressions from the convergence literature and more recent panel unit root tests to find that per capita services are converging across India's states, even as per capita incomes are not.…”
Section: Introductionmentioning
confidence: 93%